Variasi dan Komponen Makna Verba Pewarta pada Korpus Berita Daring - Herlina, Dewi; Hendrokumoro, Hendrokumoro (Humanis; Vol 28 No 1 (2024), 2024)
"Reporting verbs indicate a conversation (Romli, 2018:35). In news texts, reporting verbs are used intensively to provide information. This research focuses on the identification of variations, frequencies, and the analysis of meaning components as proposed by Nida (1975) regarding the usage of reporting verbs in online news corpus. This research uses a qualitative descriptive method with a lexical semantic approach. Data were obtained from news texts published by Kompas.com and Detik.com during August 8-10, 2023, with the theme 'Ferdy Sambo's Death Sentence Turned into Life Imprisonment.' Based on the research findings, 17 variations of reporting verbs were found in the news corpus, with the verb 'mengatakan' (to say) being the most dominant with a frequency of 83 occurrences. Meanwhile, based on the analysis of meaning components for the verbs 'mengatakan'(to say),  'menyatakan' (to state), 'menjelaskan' (to explain), and 'menyebut' (to mention), differences in usage were found through the differentiation of the meaning components of each reporting verb. This research is expected to contribute by highlighting the differences in meaning among synonymous verbs to demonstrate the diversity of the Indonesian language vocabulary.